NEW METHODS FOR TUNING OF MECHANICAL SYSTEMS DURING OPERATION IN STEADY STATE - Jaroslav HOMIŠIN (Scientific Journal of Silesian University of Technology. Series Transport)
The main purpose of this paper is to inform the technical community about new tuning methods of torsional oscillating mechanical systems (TOMS) during operation in a steady state by means of application of pneumatic flexible shaft couplings. It is possible to change the torsional stiffness of pneumatic couplings by means of a change of gaseous medium pressure either out of operation or during operation. There are two possibilities how to tune the torsional oscillating mechanical systems: - tuning of torsion oscillating mechanical systems out of operation, what fulfils condition of given system tuning, - tuning of torsion oscillating mechanical systems during operation in a steady state, what fulfils condition of given system continual tuning. The basic principle of TOMS tuning during operation in the steady state consists in an adjustment of basic dynamical properties of pneumatic coupling according to the system dynamics. This adjustment can be made by means of a regulation system working in regulation circuit arrangement with a feedback. In this way it is possible to change dynamical properties of pneumatic coupling continuously with regard to dynamic of mechanical system, so that it can be eliminated dangerous torsional oscillation of given system in the working mode.